2019
DOI: 10.7326/m18-2768
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac and Neuromuscular Features of Patients WithLMNA-Related Cardiomyopathy

Abstract: on behalf of the Italian Network for Laminopathies (NIL) † Background: Mutations in the LMNA (lamin A/C) gene have been associated with neuromuscular and cardiac manifestations, but the clinical implications of these signs are not well understood.Objective: To learn more about the natural history of LMNArelated disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 19 publications
4
47
1
Order By: Relevance
“…Although the cardiac phenotype was atypical for LMNA cardiomyopathy, the neuromuscular manifestations were similar to those commonly observed in patients with LMNA variants 11 …”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Although the cardiac phenotype was atypical for LMNA cardiomyopathy, the neuromuscular manifestations were similar to those commonly observed in patients with LMNA variants 11 …”
Section: Discussionsupporting
confidence: 57%
“…Genotype-phenotype correlation of LMNA variants involving the Arg541 residue: a case report with multimodality imaging and literature review similar to those commonly observed in patients with LMNA variants. 11 Few case reports have described patients with LMNA cardiomyopathy and missense variants involving the Arg541 residue, and all of them displayed an atypical presentation with many similarities to our case. Kwon and colleagues reported the case of an adolescent girl with the same variant as our patient, who presented with recurrent VT and had severe wall thinning and transmural LGE in the LV apex and lateral wall.…”
Section: Discussionsupporting
confidence: 55%
“…This association has not been reported in previous cohorts. Recent multicentric study reviewed the cardiac and neurologic involvement of laminopathies, concluding that most patients show neurologic symptoms by their fourth decade and develop cardiac involvement at the following decade (29). Our cohort is a bit in contrast to these data.…”
Section: Discussionmentioning
confidence: 76%
“…Patients who have both cardiac and neuromuscular manifestations more commonly experience bradyarrhythmias and atrial fibrillation compared to patients with solely cardiac phenotypes, despite having no differences in structural heart disease. In this group of patients cardiac abnormalities do not strictly correlate with the severity of the neuromuscular involvement, which may suggest distinct pathogenetic mechanisms (Benedetti et al, 2007;Hasselberg et al, 2018;Peretto et al, 2019). However, a recent study on a small cohort of patients showed that the neuromuscular presentation was associated with earlier cardiac involvement, characterized by a linear and progressive evolution from rhythm disorders to cardiomyopathy (Ditaranto et al, 2019).…”
Section: Clinical Presentationmentioning
confidence: 78%